Power law inflation with a varying condstant of gravitation and Brans-Dicke cosmology - Farhad, Abu Baker Mohammad; Azad, Abul Kalam (GANIT: Journal of Bangladesh Mathematical Society, 2012)
The homogeneous and isotropic Brans-Dicke cosmological solutions satisfying Whitrow Randalls[18] relation which have been discussed recently by Berman and Som[2] are re-examined. We extend their results and present the most general solution by solving a differential equation completely. We show that Machs assumption leads to power-law solutions in the Euclidean case. DOI: http://dx.doi.org/10.3329/ganit.v31i0.10305 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 31 (2011) 23-32